Robust Adaptive Finite-Time Synchronization of Two Different Chaotic Systems with Parameter Uncertainties - Yun-An Hu; Hai-Yan Li; Chun-Ping Zhang; Liang Liu (Journal of Applied Mathematics)
This paper is concerned with the finite-time synchronization problem for two different chaotic systems with parameter uncertainties. Using finite-time control approach and robust control method, an adaptive synchronization scheme is proposed to make the synchronization errors of the systems with parameter uncertainties zero in a finite time. On the basis of Lyapunov stability theory, appropriate adaptive laws are derived to deal with the unknown parameters of the systems. And the convergence of the parameter errors is guaranteed in a finite time. The proposed method can be applied to a variety of chaos systems. Numerical simulations are given to demonstrate the efficiency of the proposed control scheme.